Social Activities In Keraton Yogyakarta Classical Dance Studio - Dipawijaya, Pratita Sarwoadi; Adya Ratna, Rr Vegasari (Institut Seni Indonesia Yogyakarta, 2024)
This research explores the social activities in the Sanggar Tari Keraton Yogyakarta. Through interviews and literature study, this research reveals the organized social structure as well as rehearsal and performance activities that strengthen the sustainability of Yogyakarta Style Classical Dance. Collaborations with various art institutions, both local and international, are vital in expanding the cultural impact of this dance studio. Member regeneration programs such as Bedhaya Semang and Among Beksa, as well as the Caos Bekti ritual, affirm the association's commitment to maintaining Javanese dance traditions. Funding support from Dana Keistimewaan ensures the smooth operation of the studio, while the collaboration network is an important pillar in the dissemination and development of traditional arts. Thus, the social activities at the Yogyakarta Palace Dance Studio not only reflect cultural diversity, but also illustrate the ongoing efforts in the preservation and development of Indonesia's cultural heritage.